Design and analysis of the separating device for peanut half-feed combined harvesting - Li, Dongjie; Hou, Jalin; Wang, Dongwei; Gao, Zenghui; Chang, Zengcun (International Journal of Agricultural and Biological Engineering, 2025)
During combined peanut harvesting operations, the separating device plays a crucial role in determining peanuts’ damage rate and impurity content. In order to enhance the quality and efficiency of peanut harvesting, this study investigates the separating device of a two-ridge and four-row half-feeder combine harvester. Firstly, the operating principle of the separating device was analyzed, and a combined air-and-screen separating device was selected. Secondly, based on the movement state of peanut pod impurities in different sections of the separating device surface, the theoretical analysis of peanut pod impurity movement was carried out, and the peanut pod impurity dynamics model was constructed. At the same time, CFD software was used to analyze the airflow field inside the separating device. Moreover, the test factors affecting the separating effect were explored: fan wind speed, separating device surface inclination, and vibration frequency. The optimal working parameters of the device were determined as follows: a fan wind speed of 8.9 m/s, a separating device surface inclination angle of 8.3° concerning the horizontal, and a separating device vibration frequency of 7.2 Hz. The impurity content rate of the peanut pods was 1.48%, and the damage rate of the separating device was 1.61%. Finally, the impurity content of peanuts in the validation experiment was 1.53%, and the peanut damage rate was 1.68%. The effectiveness of the separating device operation was verified through field tests. The potential for further research on peanut harvesters is highlighted based on the findings of this study. Keywords: combine harvester, air-and-screen separating device, peanut, impurity content ratio, damage rateDOI: 10.25165/j.ijabe.20251801.8711Citation: Li D J, Hou J, Wang D W, Gao Z H, Chang Z C. Design and analysis of the separating device for peanut half-feed combined harvesting. Int J Agric & Biol Eng, 2025; 18(1): 92–100.